2015
DOI: 10.1017/s1049023x14001459
|View full text |Cite
|
Sign up to set email alerts
|

Building Health Care System Capacity to Respond to Disasters: Successes and Challenges of Disaster Preparedness Health Care Coalitions

Abstract: Strengthening HCCs and their underlying systems could lead to improved national resilience to disasters. However, despite many successes, coalition leaders are faced with obstacles that may preclude optimal system functioning. Additional research could: provide further insight regarding the benefit of HCCs to local communities, uncover obstacles that prohibit local disaster-response capacity building, and identify opportunities for an improved system capacity to respond to, and recover from, disasters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…Members have indicated that regional partnerships have been one of the most valuable aspects of coalition formation, and the support of day-to-day activities has been a strong motivator for participation in these coalitions. 39 Early analysis of coalitions indicates that they have a high penetration rate and can provide enough value to members to function independently of federal grant funding. 40 To date, coalitions have been focused on large-scale disaster preparedness response, and the ability of these units to capture the health and health care within a region is unknown.…”
Section: Coordination Of Health Care During Emergenciesmentioning
confidence: 99%
“…Members have indicated that regional partnerships have been one of the most valuable aspects of coalition formation, and the support of day-to-day activities has been a strong motivator for participation in these coalitions. 39 Early analysis of coalitions indicates that they have a high penetration rate and can provide enough value to members to function independently of federal grant funding. 40 To date, coalitions have been focused on large-scale disaster preparedness response, and the ability of these units to capture the health and health care within a region is unknown.…”
Section: Coordination Of Health Care During Emergenciesmentioning
confidence: 99%
“…At this time, sustainability should be on the forefront of all organizations that participate in coalitions. 4 It is very likely that non-grant-funded methods of sustainability will need to expand if coalitions are to continue in their current roles. Consequently, greater reliance on the private sector will be necessary to limit the potential loss in capacity for preparedness and response that has built up by coalitions across the nation since 2012 when ASPR formally called for the development of health care coalitions.…”
mentioning
confidence: 99%
“…For example, the US Department of Health and Human Services (HHS) Assistant Secretary for Preparedness and Response (ASPR) administers the Hospital Preparedness Program (HPP), a cooperative agreement that provides funds for health care and hospital disaster preparedness activities. These cooperative agreements are designed to develop 8 capabilities deemed essential to health care system resilience by HHS/ASPR standards: (1) health care system preparedness, (2) health care system recovery, (3) emergency operations coordination, (4) fatality management, (5) information sharing, (6) medical surge management, (7) responder safety and health, and (8) volunteer management. 3 The HPP recently required cooperative agreement recipients to develop and sustain regional health care coalitions in an effort to build locally based communities of support for disaster preparedness activities.…”
mentioning
confidence: 99%
“…3 Health care coalitions vary from region to region but can include a wide variety of stakeholders, including hospitals, community health centers, health departments, emergency management agencies, emergency medical services, and other types of health care organizations. 4,5 HPP funding has decreased dramatically in the past 10 years. This is despite recurrent calls for increased health care system disaster preparedness following significant failures of critical health care infrastructure and management during and after major disaster events such as Hurricanes Katrina and Sandy.…”
mentioning
confidence: 99%